Recent Trends in Operator Theory and Applications - Botelho, Fernanda (Contemporary Mathematics Ser., 2019)
This volume contains the proceedings of the workshop on Recent Trends in Operator Theory and Applications (RTOTA 2018), held from May 3-5, 2018, at the University of Memphis, Memphis, Tennessee. The articles introduce topics from operator theory to graduate students and early career researchers. Each such article provides insightful references, selection of results with articulation to modern research and recent advances in the area. Topics addressed in this volume include: generalized numerical ranges and their application to study perturbation of operators, and connections to quantum error c.